Prevalensi sarkopenia dan frailty di desa Pedawe, Mangupura, Serai dan Songan - I Gusti Agung Wilaja Putra; I Gusti Putu Suka Aryana; I Nyoman Astika; RA Tuty Kuswardhani; Ida Bagus Putrawan; Ketut Rai Purnami (Intisari Sains Medis, 2020)
Background: Frailty is characterized by a decrease in multi-organ physiological functions. Sarcopenia and frailty have a significant impact on individuals and society so it is necessary to know the prevalence in the community. This study aimed to determine the prevalence of sarcopenia and frailty in rural areasMethod: The was a cross-sectional study in the elderly population in the villages of Pedawa, Mangupura, Serai and Songan. Measurement of muscle mass using bioelectrical impedance analysis (BIA) and categorized based on the recommendation of the Asian Working Group for Sarcopenia (AWGS). Frailty is established through a screening questionnaire based on the Cardiovascular Health Study. The study was chosen by simple random sampling and population register data.Results: The study involved 235 elderly people with 117 people in Pedawe village, 71 people in Mangupura village, 34 people in Serai village and 13 people in Songan village with a composition of 35.5% men and 64.5% women. In this study sarcopenia in women was 51% and men 49%, while frailty was experienced in 58.9% women and 41.02% men. The mean age is 67.7 years. The prevalence of total sarcopenia is 59% with the lowest percentage ranging from the villages of Mangupura (30%), Songan (53.8%), Pedawe (70.9%), and Serai (79.4%). The overall frailty prevalence in the four villages is 17% with the percentage starting from the lowest being Mangupura (1.4%), Serai (5.9%), Songan (22.2%) and Pedawe (29.1%).Conclusions: The prevalence of sarcopenia and frailty is most common among elderly women. The highest prevalence of sarcopenia was found in Serai village and frailty prevalence was highest in Pedawe village. Latar Belakang: Frailty ditandai dengan adanya penurunan fungsi fisiologis multi organ. Sarkopenia dan frailty memberikan dampak yang bermakna bagi individu dan bagi masyarakat sehingga perlu untuk mengetahui prevalensinya di masyarakat. Penelitian ini bertujuan untuk mengetahui prevalensi sarkopenia dan frailty di daerah pedesaanMetode: Penelitian menggunakan studi potong lintang pada populasi lansia di desa Pedawa, Mangupura, Serai dan Songan. Pengukuran massa otot menggunakan bioelectrical impedance analysis (BIA) dan dikategorikan berdasarkan rekomendasi Asian Working Group for Sarcopenia (AWGS). Frailty ditegakkan melalui kuesioner skrining berdasarkan Cardiovascular Health Study. Penelitian dipilih dengan cara simple random sampling dan data register penduduk.Hasil: Penelitian melibatkan 235 orang lanjut usia dengan jumlah 117 orang di desa Pedawe, 71 orang di desa Mangupura, 34 orang di desa Serai dan 13 orang di desa Songan dengan komposisi 35,5% laki-laki dan 64,5% perempuan. Pada penelitian ini sarkopenia pada perempuan adalah 51% dan laki-laki 49%, sedangkan frailty dialami 58,9% perempuan dan 41,02% laki-laki. Rerata usia adalah 67,7 tahun. Prevalensi sarkopenia total adalah 59% dengan persentase masing-masing mulai dari yang terendah adalah desa Mangupura (30%), Songan (53,8%), Pedawe (70,9%), dan Serai (79,4%). Prevalensi frailty keseluruhan di empat desa adalah 17% dengan persentase masing-masing mulai dari yang terendah adalah desa Mangupura (1,4%), Serai (5,9%), Songan (22,2%) dan Pedawe (29,1%).Kesimpulan: Prevalensi sarkopenia dan frailty paling banyak ditemukan pada lansia perempuan. Prevalensi sarkopenia paling tinggi didapatkan di desa Serai dan prevalensi frailty didapatkan paling tinggi di desa Pedawe.